Analisis Keterlambatan Siswa Kelas X SMKS Efata dalam Menguasai Teknologi Informasi dan Komunikasi - Ariance Renda Wano; Gergorius Kopong Pati; Maria Wilda Malo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information and communication technology (ICT) is an important demand in the world of education, especially at the Vocational High School (SMK) level which prepares students to enter the digital-based world of work. However, students in class X of SMKS Efata still show delays in mastering ICT which has an impact on the learning process and their competency readiness. This study aims to analyze the factors that cause students to delay in mastering ICT as well as identify strategic steps to improve their skills. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the limitations of technology facilities, the lack of experience of students using computer devices before entering vocational schools, and the low intensity of ICT learning practices are the dominant factors that affect the delay in mastering technology. In addition, the difference in students' backgrounds in digital literacy and the lack of assistance during the learning process also slow down the development of their abilities. Nevertheless, students have good motivation to learn and adapt to technology if they are given the support of the right learning facilities and strategies. The conclusion of this study emphasizes that improving facilities, strengthening practice-based learning methods, and intensive mentoring are needed to accelerate students' ICT mastery. This research is expected to be the basis for schools in formulating ICT learning policies that are more effective and in accordance with the needs of technological developments.